Pemikiran Prof. Amin Abdullah dalam Integrasi Ilmu-Ilmu Keislaman - Qorimah, Qorimah; Baidi, Baidi (IAI Nasional Laa Roiba Bogor, 2025)
Prof. Amin Abdullah has a scientific integration mindset based on theory in accordance with understanding modern dynamics. Furthermore, Prof. Amin Abdullah has a mindset related to solving complex world problems today that cannot only be solved through the approach of one field or one discipline. The purpose of writing is to explain Prof. Amin Abdullah's thoughts in the integration of Islamic sciences. The method used is a qualitative research type through a literature review approach. The findings are that the Spider Web theory is a model integrated by Prof. Amin Abdullah. This aims to complete the science of needed connections between human reason, the universe, and the Qur'an. Based on the implementation of this theory, it can have an impact on answering the challenges of modernity and building epistemological foundations contextually, dynamically, and inclusively.